Hybrid position/force algorithms for biped locomotion - Silva, Filipe M. (2019)
This paper addresses the problem of modelling and control of a biped robot by combining Cartesian-based position and force control algorithms. The complete wlaking cycle is divided in two phases: i) single support - in which it is studied the trajectory controllability based on simple motion goals and ii) exchange of support - in which the foward leg should absorb the impact and then gradually accept the robot's weight. The contact of the foot with the constrained durface is modelled through linear spring-damper systems. The control algorithms are simulated and their effectiveness and robustness are discussed.